MBRS-63. CCR2+ HEMATOPOIETIC STEM CELLS OVERCOME TREATMENT RESISTANCE TO PD-1 IN MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Flores, Catherine; Wildes, Tyler; Drake, Jeffrey; Abraham, Rebecca; Mitchell, Duane
Abstract: INTRODUCTION: We have previously reported that different medulloblastoma models have different responsiveness to checkpoint blockade including anti-PD-1. In a preclinical model of molecular subtype sonic hedgehog (Shh) medulloblastoma (Ptc) that is completely resistant to PD-1 blockade alone, we have found that bone marrow-derived, lineage-negative hematopoietic stem and progenitor cells (HSCs) that express CCR2+ reverses treatment resistance and sensitizes mice to curative immunotherapy. METHODS: Shh molecular subtype medulloblastoma tumor cells were implanted into the cerebellum of C57BL/6 mice. Experimental groups were treated with anti-PD-1 blocking antibody (10mg/kg x 5) with or without co-transfer of syngeneic bone marrow derived HSCs. RESULTS: HSC transfer with concomitant PD-1 checkpoint blockade leads to increased intratumoral T cell frequency and activation in preclinical models of glioblastoma and medulloblastoma. Of significance, HSC transfer significantly downregulates expression of immunosuppressive markers within tumors and leads to increased gene expression of immune activation markers, but these findings are restricted to occur only within intracranial brain tumors. We have identified that CCR2+ HSCs preferentially migrate to intracranial brain tumors and differentiate into antigen presenting cells within the tumor microenvironment that cross-present tumor-derived antigens to CD8+ T cells and lead to increased antitumor immunity. In addition, HSC transfer also rescues brain tumor resistance to adoptive T cell therapy in medulloblastoma, glioblastoma, and brain stem glioma models. Our studies demonstrate a novel role for CCR2+ HSCs in overcoming brain tumor resistance to PD-1 checkpoint blockade and adoptive cellular therapy in multiple invasive brain tumor models.